2022
DOI: 10.1038/s41467-022-33334-5
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements reveal exposure risk to microplastic ingestion by filter-feeding megafauna

Abstract: Microparticles, such as microplastics and microfibers, are ubiquitous in marine food webs. Filter-feeding megafauna may be at extreme risk of exposure to microplastics, but neither the amount nor pathway of microplastic ingestion are well understood. Here, we combine depth-integrated microplastic data from the California Current Ecosystem with high-resolution foraging measurements from 191 tag deployments on blue, fin, and humpback whales to quantify plastic ingestion rates and routes of exposure. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…Plastic pollution has emerged as a pervasive global environmental threat, among which microplastics are attracting intensive attention due to their ease in spreading, uptake by various living creatures and accumulation inside biosystems [1] . The ingestion/inhalation of microplastics has been shown in a variety of organisms ranging from invertebrate [2–3] to higher plants [4–6] and mammals [7–8] . When plastic particles are further sized down to nanoplastics, they could penetrate cell membranes and initiate subcellular abnormalities [9–11] .…”
Section: Introductionmentioning
confidence: 99%
“…Plastic pollution has emerged as a pervasive global environmental threat, among which microplastics are attracting intensive attention due to their ease in spreading, uptake by various living creatures and accumulation inside biosystems [1] . The ingestion/inhalation of microplastics has been shown in a variety of organisms ranging from invertebrate [2–3] to higher plants [4–6] and mammals [7–8] . When plastic particles are further sized down to nanoplastics, they could penetrate cell membranes and initiate subcellular abnormalities [9–11] .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Notably, trophic transfer is implicated as a predominant pathway for microplastic ingestion, with larger marine mammals such as blue whale estimated to consume up to millions of microplastic particles daily. 5 A crucial subset of MPs, microfibers, 6 predominantly emanate from synthetic textiles, accounting for approximately 35% of the annual microplastic efflux into oceans. 7,8 These slender, elongated particles may exert differential ecological impacts compared to those of other geometries such as fragments or spheres.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, the ocean floor harbors over 14 million metric tons of microplastics, with a staggering 1.5 million metric tons being added each year . Microplastic ingestion has been linked to deleterious effects ranging from organ damage to suffocation, compromised growth, and reproductive fitness in aquatic organisms. , Notably, trophic transfer is implicated as a predominant pathway for microplastic ingestion, with larger marine mammals such as blue whale estimated to consume up to millions of microplastic particles daily …”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, the highest percentage of marine litter consists of plastics [ 5 , 6 , 7 , 8 ]. The major impacts of plastics on marine fauna are a result of ingestion [ 9 ], entanglement [ 10 ] and chemical pollution [ 11 ] affecting, among other things, resource acquisition, health and reproductive output [ 12 ]. Over the last half-century, along with increasing global plastic production [ 13 ], research efforts have also increased, as shown by the rising number of peer-reviewed literature and meta-analyses.…”
Section: Introductionmentioning
confidence: 99%